Plant extract activities as antioxidant and antibiofilm against chicken gut bacteria - Erika Gracia; S. Magdalena; Elizabeth Wina; Arnold P. Sinurat; Tresnawati Purwadaria (Jurnal Ilmu Ternak dan Veteriner, 2018)
The occurrence of microbial resistance against antibiotic due to the subtherapeutic dosage of antibiotic growth promoter (AGP) in poultry can be prevented by the antibiofilm substance. Plant secondary compounds have some activities like antioxidant, antimicrobial, and antibiofilm. This research was conducted to obtain the plant with the highest activity of antibiofilm and also antioxidant by analyzing several plant secondary compounds as antioxidant and antibiofilm against chicken’s gut bacteria. The tested plants were clove leaves, leaffruit plants, mangosteen peel, cashew nut shell, guava leaves, and bay leaves. These plants were extracted with methanol or n-hexane using sonication method. The antioxidant activity as the IC50 value of the plant methanol extracts were determined using α,α-diphenyl-β-picrylhydrazyl (DPPH) assay. The biofilm inhibition activity was tested against Escherichia coli, Salmonella enteritidis, and Staphylococcus aureus ATCC® 29213TM using methanol and n-hexane extracts. All of the samples had antioxidant activity. The clove leaves and leaffruit plants had the highest antioxidant activity, while mangosteen peel extract in methanol had the highest antibiofilm activity against all tested bacteria. The species of bacteria also affected the antibiofilm activity. E. coli and S. enteritidis were more resistant to antibiofilm then S. aureus. Mangosteen peel extract which showed high antioxidant and antibiofilm activity is potential to be used as a feed additive to control the pathogenic bacteria.